#### Answer

-.7

#### Work Step by Step

We know that $\sqrt .49=.7$, because $.7^{2}=.7\times.7=.49$.
Therefore, $-\sqrt .49=-(.7)=-.7$.

Published by
Pearson

ISBN 10:
0321969359

ISBN 13:
978-0-32196-935-4

-.7

We know that $\sqrt .49=.7$, because $.7^{2}=.7\times.7=.49$.
Therefore, $-\sqrt .49=-(.7)=-.7$.

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.